Amyloid myopathy mimicked with idiopathic inflammatory myopathy diagnosed using Congo red staining: a case report - Xingyu Han; Mohammadreza Kosari; Li Xu; Yue Li; Meng-ge Yang; Huajie Gao; Huizhen Ge; Bitao Bu; Suqiong Ji (BMC Neurology)
Abstract Amyloid myopathy often occurs in the context of systemic amyloidosis, as a rare manifestation of “light chain” (AL) amyloidosis, accounting for 1% of its incidence. A 58-year-old man with two years history of weakness and edema of lower extremity, elevated creatine kinase (CK), and inflammatory lesions from muscle biopsy which was misdiagnosed as inflammatory myopathy. After immunotherapy, the original symptoms worsened. We later confirmed the disease through MRI, Congo red staining and bone marrow puncture results. Our purpose is that to increase awareness of amyloid myopathy to minimize the risk of misdiagnosis and emphasize the importance of Congo red staining in diagnosing similar conditions.